PCM assisted heat pipe cooling system for the thermal management of an LTO cell for high-current profiles - Behi, Hamidreza; Karimi, Danial; Gandoman, Foad Heidari; Akbarzadeh, Mohsen; Khaleghi, Sahar; Kalogiannis, Theodoros; Hosen, Md Sazzad; Jaguemont, Joris; Van Mierlo, Joeri; Berecibar, Maitane (Case studies in thermal engineering, 2021)
This paper presents the concept of a passive thermal management system (TMS), including natural convection, heat pipe, and phase change material (PCM) for electric vehicles. Experimental and numerical tests are described to predict the thermal behavior of a lithium-titanate (LTO) battery cell in a high current discharging process. Details of various thermal management techniques are discussed and compared with each other. The mathematical models are solved by COMSOL Multiphysics®, the commercial computational fluid dynamics (CFD) software. The simulation results are validated against experimental data with an acceptable error range. Results indicate that the maximum cell temperature for the cooling strategies of natural convection, heat pipe, and PCM assisted heat pipe reaches 56 °C, 46.3 °C, and 33.2 °C, respectively. It is found that the maximum cell temperature experienced a 17.3% and 40.7% reduction by heat pipe and PCM assisted heat pipe cooling system compared with natural convection.